Water-easily dismantled adhesive and temporary adhesion method using same
By using the coordinated multimers of transition metal, phthalazine and phosphoric acid as the adhesive, the problems of difficulty in removing water of temporary adhesives and insufficient bonding strength in the prior art are solved, and the effect of efficient room temperature water removal and high bonding strength is achieved.
Patent Information
- Application Number
- JP2022150614
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-09-21
AI Technical Summary
In the prior art, temporary adhesives are difficult to completely remove in water, and the adhesive strength of the adhesive layer is insufficient.
Coordinated polyesters (CPs) containing transition metals, phthalazines and phosphoric acid are used as adhesives, and melted by heating to form an adhesive layer and removed when contacting water.
The adhesive layer formed with high bond strength at room temperature can be easily removed and is suitable for temporary bonding and disassembly.
Smart Images

Figure 0007649458000003 
Figure 0007649458000004 
Figure 0007649458000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive that can be easily dismantled with water and a temporary bonding method using the same. [Background technology]
[0002] Conventional adhesives crosslink organic polymers with covalent bonds to improve their adhesive strength, but when it comes to temporary adhesion of adherends, the adhesive layer cannot be easily removed. Also, adhesives that utilize the van der Waals forces between organic polymers have the problem that their adhesive strength is insufficient even for temporary adhesion.
[0003] Therefore, as adhesives that have relatively high adhesive strength and can be easily peeled off or removed with water, a water-easily dismantlable adhesive composition containing a 2-cyanoacrylate compound and a water-soluble compound (JP Patent Publication No. 2019-137858 (Patent Document 1)) and a temporary fixing adhesive composition containing a 2-cyanoacrylate compound having 3 to 6 1,2-alkyleneoxy structures (JP Patent Publication No. 2021-25014 (Patent Document 2)) have been proposed. However, in these adhesive compositions, the adhesive layer does not have sufficient dismantlability with water.
[0004] In addition, Yanyi Zhao et al., ACS Nano, 2017, Vol. 11, pp. 3662-3670 (Non-Patent Document 1), have investigated adhesion using Ni(H2O)2[Ni(CN)4]·4H2O, a Hoffman-type cyano-bridge coordination polymer, and have disclosed that nanoflakes of plate-like crystals of the Ni(H2O)2[Ni(CN)4]·4H2O can be used in the form of a paste to bond adherends such as glass, plastics, and metals. However, a paste-like adhesive containing a solid powder has a problem in that voids are easily formed in the adhesive layer after the solvent is removed by drying or the like, resulting in insufficient bonding strength. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-137858 A [Patent Document 2] JP 2021-25014 A [Non-patent literature]
[0006] [Non-Patent Document 1] Yanyi Zhao et al., ACS Nano, 2017, Vol. 11, pp. 3662-3670 Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made in consideration of the problems associated with the above-mentioned conventional technology, and aims to provide an adhesive capable of forming an adhesive layer that has relatively high bonding strength and can be easily dismantled with water at room temperature, and a temporary bonding method using the same. [Means for solving the problem]
[0008] As a result of extensive research to achieve the above-mentioned object, the inventors have discovered that by using as an adhesive a coordination polymer (CP) such as a metal-organic framework (MOF) which contains a transition metal, an azole, and phosphoric acid and has a melting point within a specific range, it is possible to form an adhesive layer which has relatively high bonding strength and can be easily dismantled with water at room temperature, and have thus completed the present invention.
[0009] That is, the present invention provides the following aspects.
[0010] [1] A coordination polymer containing a transition metal, an azole, and phosphoric acid and having a melting point of 80 to 700°C. the law of nature, the transition metal is at least one selected from the group consisting of Group 6 elements, Group 7 elements, Group 8 elements, Group 9 elements, Group 10 elements, Group 11 elements, and Group 12 elements; the azoles are at least one selected from the group consisting of pyrroles, diazoles, triazoles, and tetrazoles; The coordination polymer has a structure in which an organic ligand made of the azole is coordinated to the transition metal, and a polymer structure is formed by van der Waals forces and coordination bonds., Water-easily dismantled adhesive.
[0011] [2] A temporary bonding method comprising the steps of: heating the water-easily dismantlable adhesive described in [1] to a temperature equal to or higher than the melting point and lower than the decomposition point of the coordination polymer to melt the adhesive; forming an adhesive layer made of the molten water-easily dismantlable adhesive between adherends; cooling the molten adhesive layer to a temperature lower than the melting point of the coordination polymer to harden the adhesive layer; and contacting the hardened adhesive layer with water to dismantle the adhesive layer.
[0012] [3] The temporary bonding method described in [2], wherein in the step of dismantling the cured adhesive layer, the adhesive layer is subjected to ultrasonic treatment.
[0013] In the present invention, the term "easily disintegratable with water" means a property of being easily disintegrated when it comes into contact with water.
[0014] In addition, the reason why the water-dismantlable adhesive of the present invention can form an adhesive layer that has a relatively high bonding strength and can be easily dismantled with water at room temperature is not necessarily clear, but the inventors speculate as follows. That is, the water-dismantlable adhesive of the present invention contains a coordination polymer. It is speculated that this coordination polymer is capable of forming an adhesive layer with a relatively high bonding strength because the bonds constituting the coordination polymer bulk are bonded by coordination bonds stronger than van der Waals forces. In addition, when the coordination polymer comes into contact with water, the bonds between the metal nodes and the organic linkers in the coordination polymer are replaced by bonds between the metal nodes and water, so that the adhesive layer formed by the coordination polymer can be easily dismantled with water at room temperature. Note that a "coordination polymer (CP)" is a complex having a continuous structure consisting of a multidentate ligand and a metal ion, and a "metal-organic framework (MOF)" is a coordination polymer (CP) having pores. Moreover, a "metal node" is a coordinated entity consisting of a metal or a cluster containing a metal, and an "organic linker" is a ligand containing an organic compound. Effect of the Invention
[0015] According to the present invention, it is possible to form an adhesive layer that has a relatively high bonding strength and can be easily dismantled with water at room temperature. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a schematic vertical cross-sectional view showing the temporary bonded body produced in Example 1. [Figure 2A] FIG. 2 is a schematic perspective view showing the temporary bonded bodies produced in Examples 2 and 3. [Figure 2B] FIG. 2 is a schematic diagram showing an outline of the compression tests carried out in Examples 2 and 3. [Diagram 3] 1 is a graph showing the change in bonding strength due to each treatment of the temporary adhesive bodies produced in Examples 2 and 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below based on preferred embodiments thereof.
[0018] [Water-Easy Dismantling Adhesive] First, the water-dismantlable adhesive of the present invention will be described. The water-dismantlable adhesive of the present invention is made of a coordination polymer (CP) containing a transition metal, an azole, and phosphoric acid, and having a melting point of 80 to 700°C. In such a coordination polymer, an organic ligand such as an azole is coordinated to a transition metal, and a polymer structure is formed by van der Waals forces and coordination bonds. The coordination bonds are easily dissociated by water, so that an adhesive layer made of the water-dismantlable adhesive of the present invention can be easily dismantled by water at room temperature.
[0019] The transition metal is not particularly limited as long as it can be coordinated with an organic ligand such as an azole to form a coordination polymer having a predetermined melting point. From the viewpoints of environmental friendliness and rarity, preferred are Group 6 elements such as Cr, Group 7 elements such as Mn, Group 8 elements such as Fe, Group 9 elements such as Co, Group 10 elements such as Ni, Group 11 elements such as Cu, and Group 12 elements such as Zn and Cd, more preferred are Cr, Mn, Fe, Co, Ni, Cu, Zn, and Cd, and even more preferred are Zn, Co, Mn, Ni, and Cu.
[0020] The azoles are not particularly limited as long as they can be coordinated to the transition metal and form a coordination polymer having a predetermined melting point, and examples thereof include pyrroles, diazoles (e.g., imidazoles, pyrazoles), triazoles, and tetrazoles. Among these azoles, imidazoles, pyrazoles, and triazoles are preferred from the viewpoint of coordination, and imidazoles and triazoles are more preferred. In addition, examples of the imidazoles include imidazole and benzimidazole.
[0021] The coordination polymer contains phosphoric acid. By using a coordination polymer containing phosphoric acid as an adhesive, it is possible to reduce the heating temperature when melting the coordination polymer.
[0022] The coordination polymer has a melting point of 80 to 700°C. By using a coordination polymer having a melting point within such a range as an adhesive, the coordination polymer can be melted by heating, so that a molten adhesive layer can be formed, and the molten adhesive layer can be cooled and hardened to bond the adherend. In addition, since the adhesive layer can be formed without using a solvent, it is possible to prevent the generation of voids due to solvent removal, and it is possible to bond the adherend with a relatively high bonding strength. On the other hand, it is difficult to form a molten adhesive layer with a coordination polymer that does not melt even when heated, because the organic components decompose when heated. On the other hand, if the melting point of the coordination polymer is below the lower limit, it will melt even at practical room temperature, making it difficult to maintain the bonding strength. In addition, the melting point of the coordination polymer is more preferably 80 to 300°C from the viewpoints of ease of bonding formation and protection of the adherend from heat.
[0023] Specific examples of the coordination polymer that contains such a transition metal, an azole, and phosphoric acid and has a melting point within the above range include those shown in Table 1.
[0024] [Table 1]
[0025] Among these coordination polymers, from the viewpoints of low toxicity of the raw materials and ease of synthesis, azole phosphate structures (e.g., [Zn(HPO4)(H2PO4)2](ImH2)2, [Zn3(H2PO4)6(H2O)3](BImH), [Zn3(H2PO4)6(H2O)3](2-MeBImH), [Zn2(HPO4)2(H2PO4)(5-ClBImH)2](H2PO4)(MeOH)) are preferred.
[0026] The method for producing the water-dismantlable adhesive of the present invention is not particularly limited as long as it can form the coordination polymer, and for example, a method (mechanochemical method) in which the compound containing the transition metal, the azoles, and phosphoric acid are physically mixed. The mixing ratio of the compound containing the transition metal, the azoles, and phosphoric acid can be appropriately set according to the stoichiometric ratio of each component of the obtained coordination polymer.
[0027] It is also preferable to subject the thus obtained coordination polymer to vacuum drying, which allows the desorption of atmospheric gases, solvents, etc. adsorbed during synthesis. There is no particular restriction on the heating temperature during vacuum drying, but a temperature higher than the boiling points of atmospheric gases (such as water) and solvents used in synthesis is preferable.
[0028] [Temporary adhesion method] The temporary bonding method of the present invention includes a step of heating and melting the water-dismantlable adhesive of the present invention in a solid state (preferably in a sheet or powder form) at a temperature equal to or higher than the melting point and lower than the decomposition point of the coordination polymer (melting step); A step of forming an adhesive layer made of the molten water-dismantlable adhesive between adherends (adhesive layer forming step); a step of curing the molten adhesive layer by lowering the temperature to below the melting point of the coordination polymer (curing step); A step of dismantling the cured adhesive layer by contacting it with water (dismantling step); The method includes:
[0029] (Melting process) The melting step is a step of heating the water-easily dismantled adhesive in a solid state (preferably in a powder state) at a temperature equal to or higher than the melting point and lower than the decomposition point of the coordination polymer. This results in the water-easily dismantled adhesive (the coordination polymer) in a molten state. The decomposition point of the coordination polymer can be measured by thermal analysis such as thermogravimetry (TGA). There is no particular limit to the heating time, and it can be set appropriately so that the water-easily dismantled adhesive is sufficiently melted. There is no particular limit to the heating atmosphere, but an inert gas may be used in consideration of the thermal stability of the adherend.
[0030] When the solid water-easily dismantlable adhesive is heated and melted, the solid water-easily dismantlable adhesive that has been placed beforehand on the adherend may be heated and melted (melting method 1), the solid water-easily dismantlable adhesive that has been placed (sandwiched) beforehand between the adherends may be heated and melted (melting method 2), or the solid water-easily dismantlable adhesive may be heated and melted separately (without being placed on the adherend or placed (sandwiched) between the adherends) (melting method 3).
[0031] (Adhesive layer formation process) The adhesive layer forming step is a step of forming an adhesive layer made of the water-easily dismantlable adhesive in a molten state between the adherends. Specifically, in the melting step, when the water-easily dismantlable adhesive is melted by the melting method 1, the adhesive layer in a molten state can be formed between the adherends by placing another adherend on the water-easily dismantlable adhesive in a molten state. Also, when the water-easily dismantlable adhesive is melted by the melting method 2, the adhesive layer in a molten state is formed between the adherends upon completion of melting. Furthermore, when the water-easily dismantlable adhesive is melted by the melting method 3, the adhesive layer in a molten state can be formed between the adherends by applying the water-easily dismantlable adhesive in a molten state onto the adherends and placing another adherend on it.
[0032] (hardening process) The curing step is a step of lowering the temperature of the molten adhesive layer to a temperature lower than the melting point of the coordination polymer (preferably a temperature at least 30°C lower than the melting point). This hardens the adhesive layer, and the adherend is temporarily bonded by the hardened adhesive layer. When lowering the temperature of the molten adhesive layer, it is preferable to apply pressure to the adhesive layer. This makes it difficult for voids to form in the adhesive layer, improving the bonding strength. There is no particular limit to the temperature-lowering time, and it can be set appropriately so that the adhesive layer is sufficiently hardened.
[0033] (Demolition process) The dismantling step is a step of bringing the cured adhesive layer into contact with water. This allows the adhesive layer to be easily dismantled. There is no particular limitation on the method of bringing the cured adhesive layer into contact with water, and examples of the method include a method of immersing the temporary adhesive body obtained in the curing step in water, an aqueous solution or a water-containing composition, and a method of fumigating with water vapor or a gas containing water vapor. In the temporary adhesion method of the present invention, the water does not need to be heated, and water at room temperature can be used. In addition, there is no particular limitation on the contact time with water, and it can be appropriately set so that the adhesive layer is sufficiently dismantled.
[0034] In addition, in this dismantling step, it is preferable to subject the adhesive layer to ultrasonic treatment when or after the cured adhesive layer is brought into contact with water. This makes it easier to dismantle the adhesive layer. There are no particular limitations on the conditions for ultrasonic treatment, but for example, the output is preferably 100 to 2000 W and the treatment time is preferably 5 to 300 seconds. EXAMPLES
[0035] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0036] Example 1 Zinc oxide (ZnO), imidazole (ImH), and phosphoric acid (H3PO4) were weighed out in a molar ratio of 1:2:3, mixed in a mortar for 15 minutes, and the resulting mixture was vacuum dried at 100°C for 600 minutes to obtain a white powder consisting of [Zn(HPO4)(H2PO4)2](ImH2)2 (melting point: 160°C. Hereinafter abbreviated as "ZnPaIm"). The decomposition point of ZnPaIm determined by thermogravimetry (TGA) was 200°C.
[0037] Using this white powder, two aluminum plates were temporarily bonded as shown in FIG. 1. Specifically, the white powder was placed on the end (10 mm long x 17 mm wide) of an aluminum A1050 plate (adherend A, 45 mm long x 17 mm wide x 1.5 mm thick), and the white powder was melted by heating at 160°C to form a molten adhesive layer. Next, the end (10 mm long x 17 mm wide) of an aluminum A1050 plate (adherend B, 45 mm long x 17 mm wide x 1.5 mm thick) was placed on the molten adhesive layer, and a 500g weight was placed on top of it and the temperature was lowered to 25°C while applying pressure to harden the adhesive layer, and the two aluminum A1050 plates (adherends A and B) were temporarily bonded. Two such temporary adhesive bodies were produced.
[0038] A tensile test was carried out on one of the obtained temporary adhesive bodies using a tensile tester (Instron Japan Co., Ltd. "5566 Universal Tester") at a tensile speed of 1 mm / min as shown in Figure 1 to measure the tensile shear strength. The tensile shear strength of the temporary adhesive body was 2.7 MPa, which was taken as the bonding strength.
[0039] Next, a 500 g weight was attached to one end of the other temporary adhesive body (the end of the adherend A or B where the adhesive layer was not formed), and the temporary adhesive body was immersed in water at 20° C. with the weight hanging down. As a result, the adhesive layer was disintegrated within 1 second from the start of immersion.
[0040] From the above results, it was confirmed that the adhesive layer made of the water-dismantlable adhesive of the present invention has a relatively high bonding strength and is easily dismantled with water at room temperature.
[0041] Example 2 Two copper disks were temporarily bonded as shown in FIG. 2A using white powder made of ZnPaIm (melting point: 160°C, decomposition point: 200°C) prepared in the same manner as in Example 1. Specifically, the white powder was placed on the center (diameter 5 mm) of a copper C1020 disk (adherend A, diameter 10 mm, thickness 5 mm) and heated at 160°C to melt the white powder and form a molten adhesive layer. Next, a copper C1020 disk (adherend B, diameter 5 mm, thickness 2 mm) was placed on this molten adhesive layer, and the adhesive layer was hardened by lowering the temperature to 25°C while applying pressure under the weight of the adherend B, and the two copper C1020 disks (adherends A and B) were temporarily bonded. A plurality of such temporary adhesive bodies were produced.
[0042] A compression test was performed on one of the obtained temporary adhesive bodies using a compression tester (homemade using a "digital force gauge" manufactured by Imada Co., Ltd.) in air at a loading rate of 1 mm / min, as shown in Figure 2B, to measure the compressive shear strength, which was taken as the initial bonding strength. The initial bonding strength was 4.65 MPa.
[0043] Next, one of the remaining temporary adhesive bodies was immersed in tap water at 20°C for 30 minutes. The temporary adhesive body after water immersion was subjected to a compression test in the same manner as above to measure the compressive shear strength, which was taken as the bonding strength after water immersion. Table 2 and Figure 3 show the ratio of the bonding strength after water immersion to the initial bonding strength.
[0044] In addition, one of the remaining temporary adhesive bodies was immersed in water in the same manner as above, and then ultrasonic treatment was performed for 15 seconds at an output of 150 W in ion-exchanged water at 20°C using an ultrasonic cleaner ("MCD-6" manufactured by AS ONE Corporation). A compression test was performed on the temporary adhesive body after water immersion and ultrasonic treatment in the same manner as above, and the compressive shear strength was measured, which was taken as the bonding strength after water immersion and ultrasonic treatment. Table 2 and Figure 3 show the ratio of the bonding strength after water immersion and ultrasonic treatment to the initial bonding strength.
[0045] Example 3 Zinc oxide (ZnO), 1,2,4-triazole (1,2,4-Tz), and phosphoric acid (H3PO4) were weighed out in a molar ratio of 1:2:2, mixed in a mortar for 15 minutes, and the resulting mixture was vacuum dried at 100°C for 600 minutes to obtain a white powder consisting of [Zn(H2PO4)2(1,2,4-Tz)2] (melting point: 184°C. Hereinafter abbreviated as "ZnPaTz"). The decomposition point of ZnPaTz determined by thermogravimetry (TGA) was 189°C.
[0046] Using this white powder made of ZnPaTz, a plurality of temporary bonded bodies were produced in the same manner as in Example 2, except that the heating temperature during melting was changed to 185°C. The initial bond strength of one of the obtained temporary bonded bodies was measured in the same manner as in Example 2 and was 4.31 MPa. In addition, the bond strength after water immersion and after water immersion + ultrasonic treatment was measured in the same manner as in Example 2. Table 2 and Figure 3 show the ratio of the bond strength after water immersion and after water immersion + ultrasonic treatment to the initial bond strength.
[0047] Comparative Example 1 An attempt was made to prepare a temporary bonded body in the same manner as in Example 2, except that zinc 2-methylimidazole (ZIF-8, manufactured by Sigma-Aldrich Co., Ltd., hereafter abbreviated as "ZIF-8"), which is a non-melting MOF, was used instead of ZnPaIm. However, since ZIF-8 decomposed when heated, it was difficult to prepare a temporary bonded body.
[0048] Comparative Example 2 We attempted to prepare a paste-like adhesive by mixing zinc 2-methylimidazole (ZIF-8, Sigma-Aldrich) with water, but it was difficult to prepare a paste-like adhesive because ZIF-8 could not be dispersed in water.
[0049] [Table 2]
[0050] As shown in Table 2 and Figure 3, the adhesive layer made of the water-dismantlable adhesive of the present invention had a lower bond strength after immersion in water compared to the initial strength (before immersion in water), confirming that it had a relatively high bond strength and was easily dismantled by water at room temperature. Furthermore, when the adhesive layer after immersion in water was subjected to ultrasonic treatment, the bond strength was further reduced, indicating that the adhesive layer made of the water-dismantlable adhesive of the present invention can be dismantled even more easily by combining immersion in water with ultrasonic treatment. [Industrial Applicability]
[0051] As described above, according to the present invention, it is possible to form an adhesive layer that has a relatively high bonding strength and can be easily dismantled with water at room temperature.Therefore, the temporary bonding method using the water-easily dismantled adhesive of the present invention is useful as a bonding method for temporary fixing in manufacturing and inspection processes, such as temporary fixing of precision parts, cutting of silicon ingots, wafer polishing, temporary fixing in circuit formation processes, bonding materials for recycling elements on substrates, bonding materials for recycling daily necessities composites, bonding materials for recycling structural materials such as building materials and car bodies, temporary fixing for biological samples, and the like, and a bonding method for recycling processes.
Claims
1. The present invention is made of a coordination polymer containing a transition metal, an azole, and phosphoric acid, and having a melting point of 80 to 700° C. the transition metal is at least one selected from the group consisting of Group 6 elements, Group 7 elements, Group 8 elements, Group 9 elements, Group 10 elements, Group 11 elements, and Group 12 elements; the azoles are at least one selected from the group consisting of pyrroles, diazoles, triazoles, and tetrazoles; The coordination polymer has a structure in which an organic ligand composed of the azole is coordinated to the transition metal, and a polymer structure is formed by van der Waals forces and coordination bonds.
1. A water-easily dismantlable adhesive.
2. A step of heating and melting the water-dismantlable adhesive according to claim 1 at a temperature equal to or higher than the melting point and lower than the decomposition point of the coordination polymer; forming an adhesive layer between adherends, the adhesive layer being made of the molten water-dismantlable adhesive; a step of curing the molten adhesive layer by lowering the temperature to a temperature lower than the melting point of the coordination polymer; contacting the cured adhesive layer with water to disintegrate it; A temporary bonding method comprising the steps of:
3. 3. The temporary bonding method according to claim 2, wherein the step of breaking down the cured adhesive layer comprises subjecting the adhesive layer to ultrasonic treatment.
Citation Information
Patent Citations
Adhesive composition and adhesive sheet
CN111051459A
Method for peeling resin molded product composite
JP2003192827A
Conducting film and fuel battery
JP2016004621A
Proton conductor, method for producing proton conductor, and fuel cell
JP2017033704A
Easily water separable adhesive composition
JP2019137858A